2023
DOI: 10.5415/apallergy.0000000000000001
|View full text |Cite
|
Sign up to set email alerts
|

Food allergy prevention: where are we in 2023?

Abstract: Food allergy prevention involves recommendations to the maternal diet during pregnancy and breast feeding, early life feeding and introduction of solid foods. Pregnant and breastfeeding women are not recommended to exclude any food allergens from their diet, but data are lacking to support active consumption of food allergens for prevention of food allergy. Breastfeeding is recommended for the many health benefits to the mother and child but has not shown any association with reduction in childhood food allerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 152 publications
(155 reference statements)
0
3
0
Order By: Relevance
“…Additionally, recent studies suggest that the microbiome may play a role in the development of FAs [41][42][43][44][45][46]. The immunomodulatory effect of the gut microbiome may depend on its potential to produce short-chain fatty acids (butyrate, acetate, and propionate), which may protect against the development of food allergies by reducing the production of Th2-interleukins and modulating immune response in the intestine and peripheral tissues [47,48]. Since the microbiota are transferred from the mother to the child, maternal dysbiosis can be reflected in the newborn's dysbiosis, leading to FA development [49,50].…”
Section: Role Of Maternal Diet and Gut Microbiota In Allergy Developmentmentioning
confidence: 99%
“…Additionally, recent studies suggest that the microbiome may play a role in the development of FAs [41][42][43][44][45][46]. The immunomodulatory effect of the gut microbiome may depend on its potential to produce short-chain fatty acids (butyrate, acetate, and propionate), which may protect against the development of food allergies by reducing the production of Th2-interleukins and modulating immune response in the intestine and peripheral tissues [47,48]. Since the microbiota are transferred from the mother to the child, maternal dysbiosis can be reflected in the newborn's dysbiosis, leading to FA development [49,50].…”
Section: Role Of Maternal Diet and Gut Microbiota In Allergy Developmentmentioning
confidence: 99%
“…To date. diet diversity or diet indices while breastfeeding and infant food allergy have not been studied [ 92 ]. An RCT demonstrated that omega-3 fatty acid intake during pregnancy and breastfeeding reduced food allergy occurrence, yet this has not been shown exclusively in the post-partum period [ 87 , 93 ].…”
Section: Dietary Factors In Allergic Diseasementioning
confidence: 99%
“…Current discussions are focused on identifying primary prevention methods for AD and mitigating the development of additional atopic conditions, particularly food allergies in individuals with AD [ 9 , 10 ]. Furthermore, there is a growing need to adopt a multifaceted approach in identifying prenatal and dietary risk factors for AD, as well as factors influencing the development of other atopic conditions in individuals with AD [ 11 ]. Consequently, this study aims to explore prenatal and postnatal risk factors for AD development and identify individuals at heightened risk of developing other atopic conditions, specifically food allergy, through a prospective cohort study.…”
Section: Introductionmentioning
confidence: 99%